(untitled) (Research, Society and Development, 2022)
Osteonecrosis is a pathology caused by necrosis of the gnathic bones of the maxilla and mandible. Either through antiresorptive drugs or radiotherapy. L-PRF is a platelet concentrate composed of leukocytes and growth factors capable of restoring vascularization and healing of soft and hard tissues. In addition to being the newest alternative treatment for osteonecrosis. In view of this, the work aims to evaluate the effectiveness of L-PRF in the prevention and treatment of osteonecrosis, and to clarify the mechanisms of this platelet concentrate in maxillary and mandibular osteonecrosis, in addition to other therapeutic approaches combined with L-PRF. Regarding the methodology, it is based on a literature review with a qualitative approach, which used the PUBMED, Google Scholar, Medline and IBECS databases. In the initial research, it resulted in 377 articles, after applying the filters that refer to articles published between 2017 and 2022, it generated a total of 21 articles chosen. According to the literature, L-PRF is effective in osteonecrosis, however, there are differences in the literature, as well as the fact that there is still no gold standard treatment. Therefore, L-PRF is effective, but it is not yet standardized, while each case of osteonecrosis has its peculiarity. However, when combined with other forms of treatments such as human bone morphogenetic protein (PMBs), the synergistic effect of these therapeutics accelerates the patient’s healing process.